2018
DOI: 10.1088/1681-7575/aae610
|View full text |Cite
|
Sign up to set email alerts
|

An outlier-resistant indicator of anomalies among inter-laboratory comparison data with associated uncertainty

Abstract: A new robust pairwise statistic, the pairwise median scaled difference (MSD), is proposed for the detection of anomalous location/uncertainty pairs in heteroscedastic interlaboratory study data with associated uncertainties. The distribution for the IID case is presented and approximate critical values for routine use are provided. The determination of observationspecific quantiles and p-values for heteroscedastic data, using parametric bootstrapping, is demonstrated by example. It is shown that the statistic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The ratio r i = (y i − μ)/ (u 2 i + var(μ)), see for example Ref. [18] and similar definitions [19][20][21], is easy to use. A score beyond this definition for an outlier must be documented if values are discarded.…”
Section: B Estimation Of the Mean Outliers And Uncertaintiesmentioning
confidence: 99%
“…The ratio r i = (y i − μ)/ (u 2 i + var(μ)), see for example Ref. [18] and similar definitions [19][20][21], is easy to use. A score beyond this definition for an outlier must be documented if values are discarded.…”
Section: B Estimation Of the Mean Outliers And Uncertaintiesmentioning
confidence: 99%
“…This makes it important to seek alternative graphical tools that do not depend heavily on a reliable reference value. Some procedures have been suggested that address the lack of a reliable reference value by reverting to pairwise comparisons (see, for example, [9,10]), and some can provide graphical output. A plot of the median scaled difference, for example, can provide a useful indicator of location/ uncertainty anomalies without any general location estimate [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some procedures have been suggested that address the lack of a reliable reference value by reverting to pairwise comparisons (see, for example, [9,10]), and some can provide graphical output. A plot of the median scaled difference, for example, can provide a useful indicator of location/ uncertainty anomalies without any general location estimate [10]. It can, however, be useful to understand the structure and grouping of results in more detail, and for that purpose a more detailed presentation is useful.…”
Section: Introductionmentioning
confidence: 99%